Muscle hydatidosis - Almeida, Isabel; Castro, Teresa; Arévalo, Carlitos; Álvarez, Carmelo (Cirugía del Uruguay, 2002)
Muscular hydatid cysts are infrequent and consequently merit presentation of a clinica/ case. The onset of clinica/ manifestations is similar to that of a tumor of soft tissues. Diagnosis is therefore difficult and often !eads to inadequate treatment a fact which is decisive to their prognosis. An exhaustive ana!ysis of /iterature on the subject fol/ows